Reticulocytes in sports medicine - Banfi, G. (Sports Medicine, 2008)
Reticulocytes are the transitional cells from erythroblasts to mature erythrocytes. Reticulocytes are present in blood for a period of 1-4 days and can be recognized by staining with supravital dyes, such as new methylene blue, or fluorescent markers, which couple residual nucleic acid molecules, a hallmark of the immature forms of erythrocytes. Although reticulocytes could be counted through a microscope (there is a standard of International Committee for Standardisation in Haematology for manual counting), this method is reported to be time consuming, inaccurate and imprecise. The integration of the reticulocyte count in automated haematology systems allowed the widespread use of these parameters, although the lack of calibration material and different markers, technologies and software used in automated systems could engender discrepancies among data obtained from different analytical systems.